INSIGHTS INTO THE PREVALENCE AND TRANSMISSION DYNAMICS OF INFLUENZA D VIRUS AMONG MAMMALS: A MINI REVIEW (Experimental biology, 2025)
Influenza D Virus [IDV], a recently recognized member of the Orthomyxoviridae family, has attracted substantial scientific scrutiny due to its extensive host tropism, pronounced genetic heterogeneity, and potential zoonotic ramifications. Initially isolated from bovines, IDV has subsequently been identified in a diverse array of mammalian species, raising pivotal concerns regarding its epidemiological footprint, adaptive molecular evolution, and cross-species transmissibility. This mini-review aims to delineate the epidemiological distribution of IDV across mammalian hosts, elucidate its transmission dynamics, and evaluate its broader implications for both veterinary and public health sectors. A comprehensive examination of the extant literature was undertaken, with a focus on molecular epidemiology, host range plasticity, viral phylogenetics, and interspecies transmission modalities. The findings reveal that IDV predominantly circulates within cattle populations, with sporadic detections in swine, small ruminants, camelids, and, occasionally, humans. The primary modes of transmission include direct exposure to respiratory secretions, aerosolized dissemination, and fomite-mediated indirect spread...
Keywords: Influenza D Virus, mammals, prevalence, transmission, epidemiology, zoonotic potential